Being well as time goes by: future time perspective and well-being - Coudin, G. (2011)
The authors analyze data from the European Social Survey (ESS3,2006) with the framework of Socioemotional Selectivity Theory (SST, Carstensen, Fung & Charles, 2003). In order to explore the extent to which future time perspective (FTP) is related to social goals, they test SST in a representative sample of adults from of 23 countries (43000 individual responses). The study also analyses the benefits for SWB (subjective well-being) and mental health of implementing motivationally consistent social goals. The associations of FTP with age and health, as well as with expressed social goals replicate results from SST obtained in previous studies. Although SWB is higher and depression is lower when FTP is open-ended, it only increases with congruence between motivation and objectives for persons with open-ended FTP. For those with limited FTP, congruency is associated with lower SWB levels and higher depression. These results challenge the importance for well-being of congruency between FTP and social goals and stress the importance of social acceptance and autonomy for all the profiles of FTP, but especially for persons with limited future time perspective.